Azobis[tetrazolide]‐Carbonates of the Lanthanides – Breaking the Gadolinium Break. Issue 19 (14th April 2018) - Müller, Danny; Knoll, Christian; Herrmann, Andrea; Savasci, Gökcen; Welch, Jan M.; Artner, Werner; Ofner, Johannes; Lendl, Bernhard; Giester, Gerald; Weinberger, Peter; Steinhauser, Georg
Abstract : A series of rare earth element (REE) mixed‐anion 5, 5′‐azobis(1 H ‐tetrazol‐1‐ide)‐carbonate ([REE2 (ZT)2 CO3 (H2 O)10 ]· 2H2 O; REE = lanthanides plus yttrium) coordination compounds were synthesized, characterized, and analyzed. Syntheses by simple metathesis reactions under a CO2 atmosphere were carried out at ambient (La–Gd and Ho) and elevated pressures (55 bar; Tb, Dy, Er, Tm, Yb, and Y). The resulting crystalline materials were characterized principally by single‐crystal X‐ray diffraction and vibrational spectroscopy (infrared and Raman). All materials are structurally isotypic, crystallizing in the space group C 2/ c and show nearly identical spectroscopic properties for all the elements investigated. Cell parameters, bond lengths, and bond angles differ marginally, revealing only a slight variation coinciding with the lanthanide (Ln) contraction, that is, the change in the ionic radii of the trivalent rare earth elements. The herein reported series of rare earth element azobis[tetrazolide]‐carbonates represents a remarkable exception as they are a series of isotypic REE coordination compounds with tetrazolide‐derived ligands unaffected by the "gadolinium break". Abstract : Rare earth element (REE) compounds with tetrazole‐derivative anions have been prime examples of the "gadolinium break" by showing a structural discontinuity along the series after Gd. Here we present a series of REE compounds with azobis[tetrazolide] ligands that exhibit isotypic crystal structures (from Y and La to Yb) by introducing a bridging carbonato ligand. They hence "overcome" the Gd break.